Grains, grain boundaries in single and few layer MoS2 - Sobin Mathew; Vladislav Kurtash; Bernd Hähnlein; Pavithra Manoharan; Mithun Krishna; Heiko O Jacobs; Jörg Pezoldt (Nano Express, 2025)
This study investigates the chemical vapour deposition (CVD) of molybdenum disulfide (MoS _2 ) on SiO _2 , examining the formation of various grains and grain boundaries (GBs) in single- to few-layer MoS _2 . The material, optical, and electronic properties of the resulting MoS _2 were evaluated through Raman and photoluminescence (PL) spectroscopy. Notably, both Raman and photoluminescence intensities were quenched at the GBs. Moreover, a consistent redshift in the photoluminescence peak positions at the grain boundaries indicating local strain or defect-induced modifications. Electrical characterization of lateral 2-terminal backgated devices on individual grains exhibited lower carrier mobility than those fabricated on continuous few-layers MoS _2 , with the highest measured mobility reaching 18.6 cm ^2 V ^−1  s ^−1 . Additionally, the back-gated field effect transistors (FET) on individual grains and continuous fewlayered showed pronounced clockwise hysteresis in their transfer characteristics, revealing the distinctive contribution of MoS _2 surface and MoS _2 /SiO _2 interface defects and their associated traps-as primary sources of hysteresis.